2016
DOI: 10.23910/ijbsm/2016.7.4.1597
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Suitability of Fallow Lands for Major Medicinal Plants in Tamil Nadu

Abstract: The present study was carried out to assess the extent of permanent fallow lands and identify the suitability of fallow lands for cultivation of major medicinal plants viz., Aswagandha (Withania somnifera Dunal), Senna (Cassia angustifolia M. Vahl) and Tulsi (Ocimum sanctum Linn) in Nanguneri Block of Tamil Nadu during 2013-14. Indian Remote sensing satellite Resourcesat-2 LISS IV data was used to map the extent and distribution of permanent fallow lands of study area and the detailed soil survey work was carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
2
2
0
Order By: Relevance
“…The evaluation for suitability (Table 3) indicated that soils of Bareli-1 were moderately suitable with severe limitation of effective soil depth, whereas, soils of Diwartola and Bareli-3 are marginally suitable (S3) with marginal limitations of soil depth and slope, while, soils of Diwara and Bareli-2 are not suitable (N1) for growing Aswagandha due to very severe limitations of soil depth, slope and coarse fragments. Similar results of non-suitability of Ashwagandha due to shallow depth were reported by Ramamurthy and Singh (2015) and Dharumrajan et al (2016).…”
Section: Soil-site Suitability Evaluation For Medicinal and Aromatic ...supporting
confidence: 88%
See 2 more Smart Citations
“…The evaluation for suitability (Table 3) indicated that soils of Bareli-1 were moderately suitable with severe limitation of effective soil depth, whereas, soils of Diwartola and Bareli-3 are marginally suitable (S3) with marginal limitations of soil depth and slope, while, soils of Diwara and Bareli-2 are not suitable (N1) for growing Aswagandha due to very severe limitations of soil depth, slope and coarse fragments. Similar results of non-suitability of Ashwagandha due to shallow depth were reported by Ramamurthy and Singh (2015) and Dharumrajan et al (2016).…”
Section: Soil-site Suitability Evaluation For Medicinal and Aromatic ...supporting
confidence: 88%
“…The results indicated that (Table 3) soils of Bareli-1 were moderately suitable with severe limitation of effective soil depth, whereas, soils of Diwartola, and Bareli-3 are marginally suitable (S3) with marginal limitations of soil depth, slope and the soils of Diwara and Bareli-2 are not suitable (N1) for growing Tulsi due to very severe limitations of soil depth, slope and coarse fragments. The results were in close conformity with the results of Natarajan et al (2010) and Dharumrajan et al (2016). The spatial suitability maps of Lemongrass and Tulsi are presented in Figure 3a and Figure 3b.…”
Section: Soil-site Suitability Evaluation For Medicinal and Aromatic ...supporting
confidence: 86%
See 1 more Smart Citation
“…(Singh et al, 2023). Medicinal plants like Senna, Tulsi and Aswagandha provide opportunity to transferred unproductive fallow lands into productive hub for medicinal plants (Dharumarajan et al, 2016). Medicinal plants production is a profitable alternative to traditional crops (Saiyam et al, 2022).…”
Section: Introductionmentioning
confidence: 99%